Numerical modelling of the onedimensional thermoplastic coupled problem for isotropic materials using deformation theory - Y.S. Yusupov; Ch.M. Xolmatova (Genius Journals, 2023)
The coupled thermo-plastic dynamic boundary problem is formulated using the deformation theory of plasticity for small deformations. The explicit and implicit schemes of finite difference equations in one dimension case are constructed. The discreet equations are numerically solved using the explicit and implicit schemes. Comparison shows the coincidence of the numerical results received using two methods
Keywords: coincidence; implicit; deformation